Surgical Aspects in the Treatment of Adrenocortical Carcinomas in Children: Data of the GPOH-MET 97 Trial - Hubertus, J.; Boxberger, N.; Redlich, A.; von Schweinitz, D.; Vorwerk, P. (Klinische Pädiatrie, 2012)
Adrenocortical carcinomas (ACCs) are a rare entity, with an incidence of 1.5 per million population per year. The prognosis of ACC is poor. Complete surgical resection is essential for a curative approach and significantly determines overall prognosis. Tumor resection is sophisticated and complicated by the vulnerability of the tumor and its invasive growth. Chemotherapy and Mitotane are additional therapeutic approaches that are combined with surgery in an interdisciplinary strategy. In this study, 59 patients between 2 months and 18 years of age with histologically verified ACC were analyzed retrospectively with respect to oncosurgical aspects. Patients were registered in the GPOH-MET 97 trial of the Society of Pediatric Oncology and Haematology. Preoperative management, factors influencing surgical severity, and operative complications were assessed.The gender ratio was 1:2 (m:f). A total of 58 patients showed increased hormonal activity and associated clinical signs of hormonal excess. Tumor volume was ≥ 300 mL in 25 patients. These patients showed an increased rate of operative complications and a poorer overall survival (OS) rate (p<0.01). A total of 14 patients showed metastatic spread, particularly to the lungs and lymph nodes. Biopsy of the tumor was performed in 12 patients. Tumor rupture occurred in 11 patients. Preoperative biopsy and/or experienced tumor rupture were associated with poorer OS rate. R2 resection only was achievable in 5 patients, and surgery was not feasible in 3 patients.In conclusion, since most of the pediatric ACC are hormone active and can be diagnosed clinically, the need of a tumor biopsy has to be discussed critically. Thorough pre- and perioperative management is essential for oncosurgical success.
Keywords: adrenocortical carcinoma; children; surgery; tumor biopsy; tumor rupture